A Simulation Model to Analyze an Inventory System for Deteriorating Items with Service Level Constraint - Alizadeh, Mohammadmehdi; Eskandari, Hamidreza; Sajadifar, Seyed Mehdi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
In this paper an inventory system for continuous decaying items with stochastic lead time and Poisson demand is assumed. Since the products are deteriorating and demand is stochastic it is possible to deliver less than customers’ demand to them. Thus, a constraint is introduced which guarantees a specific service level. Shortages are allowed and all the unsatisfied demands are backlogged. Moreover, replenishment is one for one. Our objective is to minimize the expected long-run total cost of the inventory system. Since the stochastic lead time and service level constraint make the analytical model extremely complicated, simulation modeling approach is applied. The simulation model is validated by statistical hypothesis test for the deterministic lead time case. Then the optimizer module of the simulation software is used to find near optimal solutions for a number of examples with stochastic lead time.